Behavioral factors influencing water policy effectiveness in agriculture in Azerbaijan: a COM-B analysis and policy recommendations - Jafarli, Madina (My University, 2026)
This study looks at the behavioural factors that cause gaps in the Republic of Azerbaijan's agricultural water policy implementation. The establishment of the Azerbaijan State Water Resources Agency in 2023 and the adoption of the National Strategy for the Efficient Use of Water Resources for 2024–2040 are two significant structural reforms, but the use of water-saving technologies like drip, sprinkler, and center pivot irrigation on farms is still incredibly limited, aside from a small network of large corporate agro-parks. The primary analytical framework is the COM-B (Capability, Opportunity, Motivation → Behaviour) model, developed by Michie, van Stralen, and West (2011) as the basis for the "Behaviour Change Wheel" and enhanced by concepts from behavioural economics such as hyperbolic discounting, prospect theory, and status quo bias. Seven semi-structured interviews were conducted with experts representing water policy development, field irrigation management, large-scale commercial agriculture, smallholder farming, aquaculture and fisheries management, coordination of water resources institutions, and agricultural sector management. Thematic analysis reveals that barriers to development are related to low program coverage and opaque access to subsidies; barriers to opportunity are explained by outdated Soviet-era canal infrastructure, unstable electricity grids in villages, a lack of spare parts markets, and strong community norms regulating the canal rotation system; and motivational barriers are primarily related to loss aversion, hyperbolic discounting, and the significant erosion of institutional trust accumulated over decades of unsuccessful programs. 5 The dissertation concludes that Azerbaijan's water programs are ineffective because they are based on a rational behavior model, which assumes that only financial incentives lead to change. Based on comparative data from India, Israel, Italy, and the Netherlands, the study proposes a behavioral public policy framework that includes mandatory participation architectures, a comparative analysis of social norms, networks of demonstration projects of successful farmers, and point-of-sale subsidy structures. The most significant discovery is the need for consistency, which is absent from conventional behavioural policy recommendations: before behavioural tools can be useful, institutional authority must be restored.
Keywords: adoption of technology; institutional trust; agricultural policy; water resource management; behavioural economics; COM-B model